THE ANALYSIS OF OTORITAS JASA KEUANGAN POSITION IN THE ORGANIZATIONAL LIFE CYCLE - Stephanie Tamara Rindang; Risris Rismayani (Universitas Airlangga, 2021)
This study aims to determine the conditions and problems, as well as alternative strategies that can be providedat the Head Office of the Financial Services Authority (OJK) using the Organizational Life Cycle theory. Thepopulation of this research is the Head of OJK Employees in Jakarta as many as 72 employees. The samplingtechnique used saturated sampling method which obtained 72 respondents. The data analysis technique useddescriptive analysis assisted by Adizes Tools. The results of this study indicate that the Head Office of theFinancial Services Authority (OJK) is in a prime position. This position shows that there is a balance betweenflexibility and control, structured and systematic functions and tasks, significant leadership, quality employees,visionary innovation, and stable liquidity. However, there are several problems, namely the lack of employees,the length of the bureaucracy, inefficient structures, and differences in perceptions between OJK and the public.This problem can be overcome with alternative strategies, namely, improving communication, expertise andknowledge, utilizing technology, eliminating deficiencies in every business process, and scheduling employeeshifts to provide education to the community. The contribution of this research is expected to be able to becomea frame work on organizational life cycle knowledge, especially in the government sector, and be able to provideinformation and considerations to form alternative strategies in overcoming problems experienced in theorganizational life cycle. This research can be used as a new insight into the condition of the company from aninternal perspective.